Veliki srakoper Lanius excubitor - Podhraški, Zdravko (Acrocephalus, 1997)
A Carduelis carduelis found as Shrike's prey 8th to 13th November 1997 at Sotelsko jezero
Keywords: Great Grey Shrike; opazovanje; ornithology; ornitologija; Slovenia; Sotelsko jezero; veliki srakoper